Mucosal immunization with Ad5-based vaccines protects Syrian hamsters from challenge with omicron and delta variants of SARS-CoV-2 - Braun, Molly R.; Martinez, Clarissa I.; Dora, Emery G.; Showalter, Laura J.; Mercedes, Annette R.; Tucker, Sean N. (Frontiers in Immunology, 2023)
SARS-CoV-2 variant clades continue to circumvent antibody responses elicited by vaccination or infection. Current parenteral vaccination strategies reduce illness and hospitalization; yet do not significantly protect against infection by the more recent variants. It is thought that mucosal vaccination strategies may better protect against infection by inducing immunity at the sites of infection, blocking viral transmission more effectively, and significantly inhibiting the evolution of new variants of concern (VOCs). In this study, we evaluated the immunogenicity and efficacy of a mucosally-delivered, non-replicating, adenovirus type 5-vectored vaccine that expresses the spike (S) gene of Wuhan (rAd5-S-Wuhan), delta (rAd5-S-delta), or omicron (rAd5-S-omicron) SARS-CoV-2 VOCs. Hamsters were immunized with these vaccines intranasally prior to challenge with omicron or delta variants. Additionally, one group was vaccinated by oral gavage with rAd5-S-Wuhan prior to challenge with the delta variant. Both intranasal and oral administration of rAd5-S-Wuhan generated cross-reactive serum IgG and mucosal IgA to all variant spike and RBD proteins tested. rAd5-S-omicron and rAd5-S-delta additionally elicited cross-reactive antibodies, though rAd5-S-omicron had significantly lower binding antibody levels except against its matched antigens. Two weeks after the final vaccination, hamsters were challenged with a SARS-CoV-2 variant; omicron or delta. Whether matched to the challenge or with rAd5-S-Wuhan, all vaccines protected hamsters from weight loss and lung pathology caused by challenge and significantly reduced viral shedding compared to placebo. Vaccination with rAd5-S-Wuhan provided significant protection, although there was an improved reduction in shedding and disease pathology in groups protected by the matched VOC vaccines. Nevertheless, Wuhan-based vaccination elicited the most cross-reactive antibody responses generally. Overall, heterologous vaccination via mucosal routes may be advantageous for second-generation vaccines.